Wave diffraction of a hybrid wind turbine foundation with a double-layer aquaculture cage - Zhu, Xiaokang; Dong, Guohai; Bi, Chunwei; Zhao, Yunpeng (Frontiers in Marine Science, 2022)
A hybrid wind turbine foundation combined with a double-layer offshore net cage for marine aquaculture is proposed in this paper. To study the diffraction and hydrodynamic loads on the structure for waves with small steepness, a numerical model was established using linear potential theory and solved using the eigenfunction expansion method. A porosity parameter was introduced to describe the hydrodynamic characteristics of the net panels. The model was validated based on existing numerical results and experimental data. An empirical formula was derived to calculate the porosity parameter based on the opening ratios of the nets. The wavefield and wave force were calculated and analyzed by setting different porosity parameters, spacings between the exterior net and interior net, radius ratios of the exterior net to the wind turbine tower and thicknesses of the friction wheel. Noticeable differences in the wave elevation were observed between the upstream and downstream sides of the nets. At downstream sites, the wavefield exhibits different profiles, particularly for structures with low porosities. Sloshing modes were observed that impacted the force and wave elevation at certain frequencies. For the common fishing nets with large porosities, the spacing between the nets does not have a significant impact on the wavefield and wave force acting on the structure. Moreover, the radius and thickness of the friction wheel have a non-negligible influence on the force acting on the structure, which also narrows the intervals between adjacent sloshing frequencies. In summary, this study provides a perspective for the engineering design and hydrodynamic analysis of a hybrid wind turbine foundation with a double-layer aquaculture cage.